Free-Radical Retrograde-Precipitation Polymerization (FRRPP) Novel Concepts, Processes, Materials, and Energy Aspects - Caneba, Gerard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book pertains to unique phenomenological features of a potentially runaway polymerization reaction process that is apparently brought under control through a mass and energy confining mechanism. It integrates the combination of various concepts in order to explain a collection of experimental observations, which includes entrapment of reactive intermediates as well as their energy contents, nucleated thermal hot spots beyond adiabatic rise temperatures, and nanoscale confinement behavior that has been used for fine patterning of polymers. Toward the end, the author of the book will try to use whatever understanding that has been formulated about the Free-Radical Retrograde-Precipitation Polymerization (FRRPP) process to relate it to various materials including environmentally-reponsible and energy-relevant types, and inherent control of energetic systems.
Keywords: Chemistry; Chemistry, Physical organic; Polymers; Chemical engineering; Industrial engineering; Renewable energy sources; Nanotechnology; Chemistry; Polymer Sciences; Industrial and Production Engineering; Nanotechnology; Physical Chemistry; Renewable and Green Energy; Industrial Chemistry/Chemical Engineering